P192 QVA149 once daily provides superior bronchodilation versus indacaterol, glycopyrronium, tiotropium and placebo: the SHINE study. (19th November 2012) - Barnes, N; Bateman, E; Gallagher, N; Green, Y; Horton, R; Henley, M; Banerji, D
Abstract : Introduction: QVA149 is a novel inhaled once-daily dual bronchodilator containing a fixed-dose combination of the long-acting β2 -agonist indacaterol and the long-acting muscarinic antagonist NVA237 (glycopyrronium) in development for the maintenance treatment of COPD. This study evaluated the effect of QVA149 on lung function compared with indacaterol, glycopyrronium, open-label tiotropium and placebo in patients with moderate-to-severe COPD. Methods: This 26 week, multicentre, double-blind, parallel-group, placebo and active controlled (open-label tiotropium) study randomised male or female patients ≥40 years of age with moderate-to-severe COPD (post-bronchodilator FEV1/FVC <0.7 and FEV1 ≥30% to <80% predicted) and smoking history ≥10 pack-years to receive once-daily QVA149 (110/50µg), indacaterol (150µg), glycopyrronium (50µg), placebo (all delivered via the Breezhaler® device) and tiotropium (18µg; delivered via the Handihaler® device) (2:2:2:1:2). The primary objective was to demonstrate superiority in trough FEV1 (mean of 23h 15min and 23h 45min post-dose) of QVA149 versus indacaterol and glycopyrronium at Week 26. We also present results of trough FEV1 at Day 1 and Week 12, serial spirometry for FEV1 and forced vital capacity (FVC) at Day 1, Weeks 12 and 26. Results: Of the 2144 patients randomised, (QVA149 [n=475]; indacaterol [n=477]; glycopyrronium [n=475]; tiotropium [n=483]; placebo [n=234]), 89.1% completed the study. 75.4% were male; mean age: 63.9 years; mean post-bronchodilator FEV1: 55.2% predicted. At Day 1, Weeks 12 and 26, QVA149 was statistically superior to indacaterol, glycopyrronium, tiotropium and placebo for mean trough FEV1 and trough FVC (all p<0.001, table ). Serial spirometry in a subset of patients (QVA149 [n=66]; indacaterol [n=64]; glycopyrronium [n=63]; tiotropium [n=70]; placebo [n=31]) showed statistically significant improvements in FEV1 with QVA149 versus placebo at all time-points (p<0.001) and versus indacaterol, glycopyrronium and tiotropium at almost all assessed time-points on Day 1, and Weeks 12 and 26. Conclusion: QVA149 once daily provided significant and clinically meaningful improvements in lung function versus the component monotherapies indacaterol and glycopyrronium, as well as significant improvements versus tiotropium and placebo over 26 weeks in patients with COPD.